Jak studenci nazywają Ukraińca i Polaka (na materiale danych ankietowych z ośmiu polskich uniwersytetów) - Fyłypec, Olga (Słowo. Studia językoznawcze, 2020)
The article is devotedtothewaysinwhich Polish studentscalla Poleanda Ukrainian. The researchers (2390 surveys) wereconductedamong 1195 students from 8 Polish universities: Rzeszów University, University of Silesia, University of Wrocław, Jagiellonian University, Universityof Lodz, Adam Mickiewicz University in Poznań, Nicolaus Copernicus University in Toruń and Maria Curie- Skłodowska University in Lublin. Theresearchmaterialcovers a totalof 2946 units. Asequivalentsofthewords Pole/Ukrainian, studentsgivenamesofgeographicalcategorization–mieszkaniec Polski/ mieszkaniec Ukrainy and of politicalcategorization – obywatel Polski/obywatel Ukrainy and others. Toname a Pole, theyproposethewordsrodak, krajan, naszrealizingthe„native-foreign”opposition. There are oftenequivalentsofresearchedethnonymsintheformofdiminutives, metaphorsandanthroponyms, e.g. Polaczek, patriota, cebulak, cebula, Janusz, Grażyna, Lach. Calling a Ukrainian, such student terms dominate: sąsiad, obcokrajowiec, cudzoziemiec, rusek, ruski, Ukrainiec and others. The definition of a Ukrainian as a neighbor appears more often in the group of students from Rzeszów and Lublin and rarelyfrom Poznań, Katowice, Wrocław, Toruń, Kraków and Łódź. The spaсу location of Toruń, Łódź, Poznań and Wrocław in the West of Poland determines the perception of a Ukrainian by the students from these cities in the category East – West: ci ze wschodu, osoba ze wschodniej granicy, osoba ze Wschodu and others. Thus, the place of residenceof stereotype carriers determines the character of these latter.